INVESTIGATION OF DETERIORATION OF HYSTERETIC LOOPS IN NONLINEAR STATIC ANALYSIS (PUSHOVER) FOR SPECIAL MOMENT RESISTING FRAME WITH SHEAR WALLS - غلامرضا Ghodrati Amiri; علی Razavian Amrei; وحید Sheikhi (مجله مدل سازی در مهندسی, 2012)
Ever-increasing need of our country in studying rehabilitation of existing buildings and necessity of using applied analysis in these structures persuade us into searching in the area of effects which exist in analytical procedures. Recently, researchers have developed structures rehabilitation effectively. Their view in providing safe design of strength supply is considered to the structure`s performance. Nonlinear static procedure analysis or push over is one of the new procedures, which in spite of its high speed and simplicity of its calculation, is considered because of using FEMA356 and seismic rehabilitation code. The result of this analysis is targeted displacement which is considered as the basis for determining the structures performance and rehabilitation. If we can recognize this result exactly, it will increase the exactness of pushover analysis efficiency. Nonlinear Dynamic Analysis is the only procedures that study the effects of seismic motive on structures with the highest exactness, but it isnât as applied as pushover procedure because of wasting a lot of time, high cost and difficulty. One of the coefficients applied to determining target displacement in this procedure is C2 which is used in order to reform the effects of reducing stiffness and strength of hysteresis loops that arenât considered. In this research, It is tried to influence some reinforced concrete structures with shear walls, with different accelerations which are scaled according to FEMA356 and FEMA273 codes. These structures are designed according to the third edition of Standard 2800. At the end, the amount of C2 which is found is compared with the suggestive amount of rehabilitation code by analyzing push over and comparing its result with the result of Dynamic analysis.